Pioneer organization's activities during the first year of the restoration of Soviet power in Lithuania (1940–1941) - Savickytė, V. (Psichologija, 1963)
After the restoration of Soviet power in Lithuania the pioneer organization began to operate legally, so occupational content, format, and methods changed. Pioneers took an active part in society, i.e. the political activity of the country and expanding their activities in schools.
Keywords: pioneers and pioneer activity.